2008
DOI: 10.1016/j.juro.2008.03.043
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nomogram to Predict the Probability of Prostate Cancer on Repeat Biopsy

Abstract: We successfully developed an accurate model to predict the outcome of repeat prostate biopsy. Adding the free-to-total prostate specific antigen ratio, digital rectal examination, prostate specific antigen and slope, and history of high grade prostatic intraepithelial neoplasia sharply improves the accuracy of our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…While there have been nomograms derived from these studies, they offer conflicting evidence on the role of PSA and its calculated kinetics (e.g. doubling time) in predicting prostate cancer in the repeat biopsy setting (Moussa et al 2010; Benecchi et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…While there have been nomograms derived from these studies, they offer conflicting evidence on the role of PSA and its calculated kinetics (e.g. doubling time) in predicting prostate cancer in the repeat biopsy setting (Moussa et al 2010; Benecchi et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, prospective trials have failed to demonstrate an association between the presence of HGPIN at initial PBx and subsequent PCa at repeat PBx [33,34,35]. Conversely, Benecchi et al [36], Rochester et al [37] and Netto and Epstein [38] have identified the presence of HGPIN as a risk factor in their analyses and included HGPIN in their novel repeat PBx nomograms.…”
Section: Resultsmentioning
confidence: 99%
“…The combined use of multiple predictive factors has been designed and nomograms for repeat biopsy were reported, including many weighted markers such as age, digital rectal examination, PSA, prostate volume, PSA density, PSA TZ density, F/T, family history and initial biopsy findings [10,11,34,35]. Using these nomograms, the accuracy of cancer detection was approximately 70-80%.…”
Section: Discussionmentioning
confidence: 99%